Evaluation of Long-Term Unemployment Trends and Regional Differences in Lithuania - Pocius, Arūnas; Miežienė, Rasa (Lithuanian Journal of Statistics, 2018)
[full article and abstract in Lithuanian; abstract in English] This article is based on the results of the project ‘Regional disparities of welfare in Lithuania’ (project number GER-005/2017) of the National Research Programme ‘Welfare society’. The project was funded by the Lithuanian Research Council. The aim of the publication is to analyse the trends of long-term unemployment in Lithuania, as well as to assess differences in the context of other EU countries. The main priority of this publication is the assessment of regional differences of long-term unemployment in Lithuania – the data are analysed in urban and rural areas, as well as in different municipalities of Lithuania. In the course of the analysis, data from Statistics Lithuania, Eurostat and Employment Service were used.